MANAGEMENT OF RURAL ACTIVITY: A STUDY AMONG BUYERS OF AGRICULTURAL MACHINERY VISITORS EXPOINTER - ESTEIO/RS - Guse, Jaqueline Carla; Dörr, Andréa Cristina; Rossato, Marivane Vestena; Freitas, Luiz Antônio Rossi de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708776 Considering the great social and economic importance of the agribusiness, this research seeks to identify thedeterminant factors that influence the most the decision taking of rural producers on agricultural machineries. Inorder to achieve this objective, an analysis of the decision making procedure was done by rural producers, identifyingtheir profile and which factors are the most relevant in the moment of purchasing. Initially, we did an overview of theindustry and agricultural implements in Brazil and in the Rio Grande do Sul state and show its statistics of productionand sales. The methodology used is this research is based on an exploratory study through field research conductedon August, 28, 2011 at the International Exposition of Animals, Machineries, Implements and Rural Products(EXPOINTER) – Esteio-RS through the application of a semi-structured questionnaire. It is concluded that the mainfactors that determine the choice are related with the operational procedure, trust on label, friends and experts’opinion and the financing form.